Fiber-reinforced composites in dentistry – An insight into adhesion aspects of the material and the restored tooth construct. Issue 2 (February 2023) - Khan, Aftab Ahmed; Zafar, Muhammad Sohail; Fareed, Muhammad Amber; AlMufareh, Nawaf Abdulrahman; Alshehri, Faisal; AlSunbul, Hanan; Lassila, Lippo; Garoushi, Sufyan; Vallittu, Pekka Kalevi
Abstract: Objective: This review aimed to highlight the insight into adhesion aspects within the components of the glass FRC (i.e ., fiber and matrix) and between resin luting material and the glass FRC construction. Methods: The fundamentals of semi-interpenetrating polymer network (semi-IPN) based FRCs and their advantages in forming a solid adhesive interface with indirect FRC restoration, dental adhesive, and luting cement are elaborated. The important resin matrix systems and glass fibers used in FRCs are discussed. This is principally based on a survey of the literature over Medline/PubMed, Web of Science, and Scopus databases and a review of the relevant studies and publications in scientific papers in international peer-reviewed journals for the specific topic of biomaterials science. The keywords used for the search approach were: adhesion, fiber-reinforced composite, glass fiber, and semi-interpenetrating polymer network. Results: The polymer matrix systems of semi-IPN-based FRCs and formation of secondary-IPN layer are pivotal for bonding of multiphasic indirect dental constructs and repair. Additionally, describing areas of indication for FRCs in dentistry, explaining the adhesion aspects of FRC for the cohesion of the material itself, and for obtaining durable adhesion when the FRC construct is luted to tooth and remaining dentition. Current progress in the field of FRC research and future directions are summarized and presented. Significance: By understanding the isotropic-anisotropic nature of fibers and the interfacial adhesion within the components of the FRC; between resin cement and the FRC construction, the clinically successful FRC-based multiphasic indirect tooth construct can be achieved. The interfacial adhesion within the components of the FRC and between resin luting material and the FRC construction play a key role in adhesion-based unibody dental restorations.